Haste to the Battle : A Marine Commando at War - Moulton, J. L. (London Cassell & Company Ltd., 1963)
A personal account of the author's experiences while serving as the Commanding Officer of No. 43 Royal Marine Commandos during World War II.
Include Illustrations, Appendix and Index.
With a preface by General Sir Richard Gale.
Keywords: World War (1939-1945) -- Great Britain. Royal Marines